Friends or Enemies? Spanish Captives in France, 1809-1814 - Zozaya-Montes, Maria (2014)
The Napoleonic wars in certain countries have created common stereotypes. Predominantly, that one between the Spanish and French Nation has spread an image of absolute enmity of the French. If we study some examples deeply, particularly that of the elite prisoners who went to the next door country, we see how that hostility images are very different of the general image which is predominant on the official History.